Clinical effectiveness and safety of vedolizumab versus infliximab in biologic-naïve patients with ulcerative colitis: A comparative real-world multicentric observational study - da Costa Ferreira, Sandro (2025)
Objective: Vedolizumab (VDZ) and infliximab (IFX) are first-line therapies for moderate-to-severe ulcerative colitis (UC). Despite their widespread use, there are no direct comparative studies, and real-world data, particularly in Latin America, are limited. This study compared the effectiveness and safety of VDZ and IFX in biologic-naïve UC patients. Methods: This retrospective cohort study included patients with moderate-to-severe UC (Mayo score 6–12, endoscopic sub-score ≥2) treated with VDZ or IFX. Primary endpoints were clinical remission (partial Mayo score ≤2), endoscopic remission (Mayo sub-score = 0), and steroid-free clinical remission at week 52. Secondary endpoints included clinical response, endoscopic response, biological therapy optimization, adverse events (AEs), hospitalizations, and biochemical remission at week 52. Propensity score adjustment (1/PS) was used to adjust for potential confounders. Results: A total of 297 UC patients (156 IFX, 141 VDZ) were analyzed. Clinical remission at week 52 was 82.3% for VDZ and 77.6% for IFX (p = 0.11), while endoscopic remission was higher in VDZ patients (47.4% vs. 33.1%, p = 0.03). Steroid-free clinical remission rates were similar between groups (p = 0.98). Endoscopic response at week 52 favored VDZ (78.4% vs. 62.7%, p < 0.001), and VDZ had higher treatment persistence (80.8% vs. 61.8%, p < 0.001). AEs and hospitalizations were more frequent in IFX patients (p < 0.001). Conclusions: Both VDZ and IFX are effective in biologic-naïve UC patients, however VDZ demonstrated superior endoscopic outcomes, higher treatment persistence, and a better safety profile, supporting its use as a first-line therapy.